2019
DOI: 10.3390/medicina55050186
|View full text |Cite
|
Sign up to set email alerts
|

High HOMA-IR Index in Healthcare Shift Workers

Abstract: Background and objectives: Evidence shows that shift work may be correlated with insulin resistance (IR). Therefore its estimation in clinical and prevention practice is of great significance. A cross-sectional study was performed to examine the Homeostasis Model Assessment-Insulin Resistance (HOMA-IR) Index among healthcare shift workers (HCSW). Materials and Methods: A total of 272 healthcare workers (HCWs) were invited to participate in the study within an occupational surveillance framework, 137 were HCSW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…The factors involved in these responses may be different. In addition to sleep deprivation, it is believed that the particular psychophysical commitment required by the activity conducted on the road plays a fundamental role [49][50][51][52][53][54]. Previous research indicated that exposure to shift work during one's occupational career causes disruption of the circadian time.…”
Section: Discussionmentioning
confidence: 99%
“…The factors involved in these responses may be different. In addition to sleep deprivation, it is believed that the particular psychophysical commitment required by the activity conducted on the road plays a fundamental role [49][50][51][52][53][54]. Previous research indicated that exposure to shift work during one's occupational career causes disruption of the circadian time.…”
Section: Discussionmentioning
confidence: 99%
“…In a highly precarious and highly conflictual work environment, workers' situations of psychophysical discomfort tend to grow exponentially, undermining not only the physical integrity of a worker but, above all, his/her balance and emotional stability [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Several indications in the literature have shown that, apart from socio-demographic factors and personality traits, circumstantial emotional states especially condition the perception of risk at work [78,79]. Some authors have described risk perception as a cognitive process mediated by an emotional component: emotions would represent heuristics (or mental shortcuts) that allow people to assess risks in a way that is certainly not rational, but functional [80,81,91]. Clearly, these temporary emotional states are mainly conditioned-and somehow managed-by our personality structure, but it will be the task of future research to clarify the weight of the different variables in the perception of negative actions and work-related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Shift work may disrupt sleep and meal rhythms. The perturbation of biological rhythms can alter metabolic homeostasis that may lead to weight gain and/or metabolic disturbances [54][55][56][57]. Shift work was associated with higher waist circumference [58][59][60], and a higher risk of metabolic syndrome and cardiovascular events [7,[61][62][63].…”
Section: Discussionmentioning
confidence: 99%